Ответы и объяснения

2013-01-29T20:31:03+04:00

 25^(х^2+0.5) - 5^x^2=5^(x^2+3) - 25

  5^(2х^2+1) - 5^x^2=125 * 5^x^2 - 25 

  5*5^2х^2 - 5^x^2 - 125 * 5^x^2 + 25  =0

  5*5^2х^2  - 126 * 5^x^2 + 25  =0 

Пусть  5^x^2  = а,тогда

5a^2-126a+25=0

a1=0,2=1/5

a2=25

так как  5^x^2  = а, то

1) при а1=1/5=5^(-1)        5^x^2=  5^(-1), тоесть  х^2 = -1 - такого не может быть

2) при а2=25= 5^2             5^x^2=  5^2, тоесть  х^2 = 2, 

     тогда  х1= корень(2)

                 х2= - корень(2)

 Надо найти х1+х2=  корень(2) + (-  корень(2))=0

 

 Ответ: 0